2022
DOI: 10.1186/s12884-021-04373-5
|View full text |Cite
|
Sign up to set email alerts
|

Using deep learning to predict the outcome of live birth from more than 10,000 embryo data

Abstract: Background Recently, the combination of deep learning and time-lapse imaging provides an objective, standard and scientific solution for embryo selection. However, the reported studies were based on blastocyst formation or clinical pregnancy as the end point. To the best of our knowledge, there is no predictive model that uses the outcome of live birth as the predictive end point. Can a deep learning model predict the probability of live birth from time-lapse system? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A study on willingness of the floating population to have a second child in Hunan Province found that the relevant factors of fertility willingness included gender, age, occupation, education level, and marital status ( 15 ). Logistic regression, neural networks, and other machine learning models had been used to predict the birth results of pregnant women ( 16 ) and live birth results of embryos ( 17 ). However, there was still a lack of model research used to predict the fertility behavior of the floating population.…”
Section: Introductionmentioning
confidence: 99%
“…A study on willingness of the floating population to have a second child in Hunan Province found that the relevant factors of fertility willingness included gender, age, occupation, education level, and marital status ( 15 ). Logistic regression, neural networks, and other machine learning models had been used to predict the birth results of pregnant women ( 16 ) and live birth results of embryos ( 17 ). However, there was still a lack of model research used to predict the fertility behavior of the floating population.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, assisted reproductive technologies have bene ted from the increased use of arti cial intelligence techniques such as DL and image segmentation 34,[48][49][50][51][52][53] , although segmenting images of bovine COCs had not been done yet. AIxpansion was therefore developed to automatically measure the area of immature and mature bovine COCs by image segmentation, and to consequently calculate the relative expansion of the cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Parallel efforts took advantage of the size of the available time-lapse datasets to train convolutional neural network (CNN) based classifiers that assess embryo potential using the raw video files in an unbiased annotation-independent manner. 26,27 However, training such deep learning models is challenging due to the size of the video files (~100's Mb), which would require a sufficiently large sample number. 28,29 Morphokinetic evaluation of the developmental potential proved highly efficient in de-selecting for transfer poor quality embryos.…”
Section: Introductionmentioning
confidence: 99%